Jejunal diverticula with perforation in non steroidal anti inflammatory drug user: A case report - Gupta, Shobhit (Int J Surg Case Rep, 2017)
INTRODUCTION: Multiple diverticulosis of the jejunum constitutes an uncommon pathology of the small bowel. The disease is often asymptomatic and must be taken into consideration in cases of unexplained malabsorption, anemia, chronic abdominal pain and discomfort. CASE PRESENTAION: We are thereby reporting a 50 yr patient on chronic NSAID ingestion presenting to us with acute abdomen. On exploration, there were multiple (14) jejunal diverticuli on both mesenteric and antimesentric border from 10 cm to 90 cm distal to duedenojejunal junction with a perforation in one of the diverticulum, 80 cm distal to the ligament of Treitz. We performed a resection of a 80-cm jejunal segment involving the multiple diverticula and an end to end jejunojejunostomy. DISCUSSION: Drug-induced jejunal perforation is known, but jejunal diverticular perforation related to steroid/treatment has been reported only once previously. Long-term NSAID therapy usually induces clinically silent enteropathy characterized by increased intestinal permeability and inflammation. Jejunal diverticulosis is a challenging disorder from a diagnostic perspective, with no truly reliable diagnostic tests. The current treatment of choice for perforated jejunal diverticula causing generalized peritonitis is prompt laparotomy with segmental intestinal resection and primary anastomosis. CONCLUSION: Jejunal diverticula are rare lesions, and their perforation never features in the list of diagnoses for acute abdomen, especially in this part of the world. Further this unique case report opens the doors for further research to prove an assosiation between NSAID use and diverticular perforation which itself is a very rare entity.